2018
DOI: 10.1177/0363546518782939
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Recipient Anteroposterior Mismatch Does Not Affect the Midterm Clinical Outcomes of Osteochondral Allograft Transplantation of the Femoral Condyle

Abstract: Background: For the treatment of femoral condyle cartilage defects with osteochondral allograft transplantation (OCA), many surgeons have relaxed their graft-recipient size-matching criteria given the limited allograft supply. However, since the anteroposterior (AP) length is typically correlated with the radius of curvature for a given condyle, a large mismatch in graft-recipient AP length can indicate a corresponding mismatch in the radius of curvature, leading to articular incongruity after implantation. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…A recent clinical study showed that graftrecipient anteroposterior mismatch was not associated with OCA failure or patient outcomes, suggesting that anteroposterior length mismatch is not an absolute contraindication for graft acceptance. 82 With regard to cartilage viability, all experts concurred that a standardized method for testing cartilage viability and metabolic activity should be established. Chondrocyte viability is considered critical for durable osteochondral restoration, survivorship, and long-term outcomes.…”
Section: Graft Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent clinical study showed that graftrecipient anteroposterior mismatch was not associated with OCA failure or patient outcomes, suggesting that anteroposterior length mismatch is not an absolute contraindication for graft acceptance. 82 With regard to cartilage viability, all experts concurred that a standardized method for testing cartilage viability and metabolic activity should be established. Chondrocyte viability is considered critical for durable osteochondral restoration, survivorship, and long-term outcomes.…”
Section: Graft Matchingmentioning
confidence: 99%
“…20,58,80,83,88 0 0 1 0 4 5 C Femoral condylar OCAs can be adequately size matched using condylar and/or tibial width measured on radiographs with magnification marker or MRI/CT. 20,82 0 respondents agreed that rehabilitation after OCA reconstruction of the patellofemoral region should include weightbearing as tolerated in conjunction with extension bracing (up to 6 weeks). This consensus group agreed that time (minimum 12 weeks from surgery) and functional recovery should both be used as criteria to return to loading activities.…”
Section: Rehabilitation and Return To Sportsmentioning
confidence: 99%
“…29 Knowledge surrounding OCAs and cartilage restoration techniques for the knee continues to grow. As an example, Wang et al 26,27 demonstrated that condyle-specific matching and a graft-recipient anteroposterior mismatch of 6.7 mm were not associated with midterm OCA failure rates or inferior patient-reported outcome measures (PROMs). Beyond evaluating the success of OCAs in terms of technique, graft survival rate, or statistical changes in PROMs, Williams et al 29 first quantitatively defined clinical significance after mosaicplasty (osteochondral autograft transfer) and OCA of the knee in terms of clinically meaningful improvements: the minimal clinically important difference (MCID) and substantial clinical benefit (SCB).…”
mentioning
confidence: 99%
“…6 Matching a graft to its donor site with respect to size and topography is important to minimizing articular step-off and maintaining near-normal contact pressure. 26 Studies have shown that an elevation of even 0.5 mm to 1 mm over the adjacent articular cartilage at the distal femur can increase contact pressures on the graft up to 50%. 27,28 In an effort to optimize articular congruity, many surgeons therefore seek hemicondyle grafts matched to the host laterality, mediolateral dimension, and anteroposterior dimension.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In an effort to optimize articular congruity, many surgeons therefore seek hemicondyle grafts matched to the host laterality, mediolateral dimension, and anteroposterior dimension. 26,29 A few studies have investigated the role of graft subchondral bony thickness in outcomes of OCA. Ackerman et al 30 showed that grafts with bony thickness <5 mm had 4.9 times greater odds of demonstrating subchondral cystic changes at short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%